Ответы и объяснения

Лучший Ответ!
  • Участник Знаний
2014-01-13T12:04:26+00:00
1) ( Х - 7 ) * ( Х + 2 ) = 2 
X^2 + 2X - 7X - 14 - 2 = 0
X^2 - 5X - 16 = 0
D = 25 - 4*1*(-16) = 25 + 64 = 89 ; V D = 9.43398 ( округляем до 9 ) 
X1 = ( 5 + 9 ) : 2 = 14 : 2 = 7
X2 = ( 5 - 9 ) : 2 = ( - 2 )
Ответ: ( - 2 ) ; 7
.....................................................................................
2) 0.8X - 28 - 1.5X - 30 - 3 = 0
- 0.7X - 61 = 0
- 0.7X = 61 
X = ( - 87.14285 ) округляем до ( - 87 )
Ответ: ( - 87 )